2005
DOI: 10.1080/17453670510045309
|View full text |Cite
|
Sign up to set email alerts
|

Do non-steroidal anti-inflammatory drugs cause endoprosthetic loosening? A 10-year follow-up of a randomized trial on ibuprofen for prevention of heterotopic ossification after hip arthroplasty

Abstract: Background Non-steroidal anti-inflammatory drugs (NSAIDs) are known to be potent inhibitors of new bone formation. We investigated whether NSAIDs given at surgery influence the long-term results after total hip arthroplasty (THA).Patients and methods We performed a 10-year follow-up on 142 of 144 patients who had taken part in a randomized trial on the preventive effects of the NSAID ibuprofen on heterotopic ossification after THA. 96 patients were treated with ibuprofen: 48 for 1 week postoperatively, 48 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…Similarly, Kjaersgaard-Andersen et al (1991) could not detect a difference in loosening or lucencies between patients who received indomethacin and the ones who did not. On the other hand, Persson et al (2005a) found a trend of higher revision rates in an indomethacin treatment group than in patients who did not receive any NSAIDs after 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, Kjaersgaard-Andersen et al (1991) could not detect a difference in loosening or lucencies between patients who received indomethacin and the ones who did not. On the other hand, Persson et al (2005a) found a trend of higher revision rates in an indomethacin treatment group than in patients who did not receive any NSAIDs after 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 76%
“…Theoretically, these NSAIDs inhibit bone restoration, which may result in a less stable or unstable implant (Persson et al 2005a). The effect of NSAIDs could be even more devastating if they are combined with bone grafts to reconstruct bone defects.…”
mentioning
confidence: 99%
“…We were unable to find data on potential long-term complications of radiation or NSAIDs. However, the existence and clinical meaning of suggested potential long-term complications, such as soft tissue or osseous malignancies attributable to radiation [16,17] or prosthetic loosening attributable to NSAIDs [26], are more than questionable, especially considering the prohibitively long latencies of such events at the average age of most patients undergoing hip surgery. A recent study reported no increase in implant migration after 5 years in patients who had received NSAIDs or radiation to prevent HO [13].…”
Section: Discussionmentioning
confidence: 99%
“…The difference was not statistically significant, but reduced functional results with Brooker grade 3 and 4 ectopic bone formation have been shown by Hirota et al (1997). NSAIDs given prophylactically reduce ectopic bone formation, but they may have a negative effect on results in the longer term (Persson et al 2005).…”
Section: Osteolysis Wear and Looseningmentioning
confidence: 99%